2015
DOI: 10.1016/j.jmaa.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear maps preserving Jordan triple η-⁎-products

Abstract: Let η = −1 be a non-zero complex number, and let φ be a not necessarily linear bijection between two von Neumann algebras, one of which has no central abelian projections, satisfying φ(I) = I and preserving the Jordan triple η- * -product. It is showed that φ is a linear * -isomorphism if η is not real and φ is the sum of a linear * -isomorphism and a conjugate linear * -isomorphism if η is real.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…They were extensively studied because they naturally arise in the problem of representing quadratic functionals with sesquilinear functionals (see [17][18][19]) and in the problem of characterizing ideals (see [2,16]). Particular attention has been paid to understanding maps which preserve the skew Lie product or the Jordan * -product on * -algebras (see [1,3,4,7,9,12,13]).…”
Section: Introductionmentioning
confidence: 99%
“…They were extensively studied because they naturally arise in the problem of representing quadratic functionals with sesquilinear functionals (see [17][18][19]) and in the problem of characterizing ideals (see [2,16]). Particular attention has been paid to understanding maps which preserve the skew Lie product or the Jordan * -product on * -algebras (see [1,3,4,7,9,12,13]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Huo et al in [5] studied a more general problem. They considered the Jordan triple η- * -product of three elements A, B, and C in a * -algebra A defined by A♦ η B♦ η C = (A♦ η B)♦ η C (we should be aware that ♦ η is not necessarily associative).…”
Section: Introductionmentioning
confidence: 99%
“…So, the class of those maps preserving the Jordan triple η- * -product is, in principle, wider than the class of maps preserving the Jordan η- * -product. In [5], let η = −1 be a nonzero complex number, and let Φ be a bijection between two von Neumann algebras, one of which has no central abelian projections, satisfying Φ(I) = I and preserving the Jordan triple η- * -product. In [5] it was shown that Φ is a linear * -isomorphism if η is not real and that Φ is the sum of a linear * -isomorphism and a conjugate linear * -isomorphism if η is real.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, [5] did not include the case η = −1. Obviously, the Jordan (triple) (−1)- * -product is very important and meaningful.…”
Section: Introductionmentioning
confidence: 99%